Aggregate Uncertainty and the Supply of Credit - Valencia, Fabian (Washington, D.C. : International Monetary Fund, 2013)
Recent studies show that uncertainty shocks have quantitatively important effects on the real economy. This paper examines one particular channel at work: the supply of credit. It presents a model in which a bank, even if managed by risk-neutral shareholders and subject to limited liability, can exhibit self-insurance, and thus loan supply contracts when uncertainty increases. This prediction is tested with the universe of U.S. commercial banks over the period 1984-2010. Identification of credit supply is achieved by looking at the differential response of banks according to their level of capitalization. Consistent with the theoretical predictions, increases in uncertainty reduce the supply of credit, more so for banks with lower levels of capitalization. These results are weaker for large banks, and are robust to controlling for the lending and capital channels of monetary policy, to different measures of uncertainty, and to breaking the dataset in subsamples. Quantitatively, uncertainty shocks are almost as important as monetary policy ones with regards to the effects on the supply of credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet